1994
DOI: 10.1118/1.597350
|View full text |Cite
|
Sign up to set email alerts
|

Absorbed dose perturbation caused by diodes for small field photon dosimetry

Abstract: Uncertainties in dose measurements which may be considered acceptable for standard radiotherapy techniques may not be acceptable for radiosurgery or other precision radiotherapy techniques. One example of this type of uncertainty are the small perturbations to measured dose distributions which are caused by the use of diode detectors. In this article the effect of using diodes to measure small field penumbra is assessed and comments are made about diode orientation and diode construction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 0 publications
4
56
0
Order By: Relevance
“…The diode must be used carefully because it can perturb the profiles depending on the direction of its axis with respect to the direction of scanning and on the presence of a metal shield for scattered photons. 66,67 On the other hand, radiographic films are affected by nonuniform spectral sensitivity, 68 and radiochromic films show a statistical uncertainty that is too high to allow small variations of the FWHM to be detected. 7 The profile-matching method is not able to account for small variations of the FWHM because of two types of uncertainty: the detector's characteristics that can influence the measurement of the profile [69][70][71][72] and the statistical uncertainty of the Monte Carlo simulation.…”
Section: Discussionmentioning
confidence: 99%
“…The diode must be used carefully because it can perturb the profiles depending on the direction of its axis with respect to the direction of scanning and on the presence of a metal shield for scattered photons. 66,67 On the other hand, radiographic films are affected by nonuniform spectral sensitivity, 68 and radiochromic films show a statistical uncertainty that is too high to allow small variations of the FWHM to be detected. 7 The profile-matching method is not able to account for small variations of the FWHM because of two types of uncertainty: the detector's characteristics that can influence the measurement of the profile [69][70][71][72] and the statistical uncertainty of the Monte Carlo simulation.…”
Section: Discussionmentioning
confidence: 99%
“…The small width of the silicon diode's depletion zone, when it is aligned with its stem perpendicular to the beam, might be thought to make this orientation preferable. However, electron ranges in the material behind the depletion zone are shorter than those in the water in front of it, asymmetrizing the sensitivity of the diode in this perpendicular orientation and leading to asymmetries in measured penumbra widths and shapes as described by Beddar et al 14 For the perpendicular diode orientation, we have found that penumbra widths measured as the diode exits the beam ͑Fig. 3͒ are around 0.2 mm larger than widths measured as the diode enters the beam.…”
Section: Iib2 Measurementsmentioning
confidence: 82%
“…The diodes should be evaluated for potential dose perturbation based on their respective construction. 22 It is not recommended to use chambers, even microchambers, for output factor measurements below collimator sizes of 20 mm.…”
Section: Iib2 Monthly Accelerator Qamentioning
confidence: 99%